Vascular epiphytes in urban trees in Goiânia city, Brazilian Cerrado - Figueiredo, Talita Nunes de Castro; Ferreira, Jorge Luís Sousa; Calil, Francine Neves; Borges, Jácomo Divino; e Silva Neto, Carlos de Melo (Revista Ecologia e Nutrição Florestal - ENFLO, 2021)
The objective of this study was to evaluate the presence of epiphyte species in trees that compose the urban trees of four avenues of Goiânia city – state of Goiás. All individuals from the avenue median and sidewalks were quantified, all epiphyte host individuals were inventoried and the epiphytes found were evaluated qualitatively and quantitatively. The species Ficus rubiginosa was present in 68.63% of the cases, followed by Ficus luschnathiana (15.69%), Ficus insipida (5.88%) and Ficus guaranitica (5.88%). A total of 84.62% of the hosts are Poincianella pluviosa, 51.92% are individuals of height between 14 and 16 meters and 35.29% have a diameter between 46.00 and 61.99 cm. The hemiepiphytes occurred on Libidibia ferrea, Ceiba speciosa, Albizia lebbeck and Pachira aquatica. The occurrence of hemiepiphytes prevailed on trunk bifurcations (44.23%), branch bifurcation (19.23%), branch hollows (17.31%) and on branches and roots (3.85%). About 15.65% of each adult arboreal in Goiânia city is inferred to hold at least one epiphyte.